2020
DOI: 10.1080/02656736.2019.1708483
|View full text |Cite
|
Sign up to set email alerts
|

One-lung ventilation for percutaneous thermal ablation of liver tumors in the hepatic dome

Abstract: Purpose: To investigate the feasibility, efficacy and safety of one-lung ventilation for percutaneous thermal ablation of liver tumors in the hepatic dome. Materials and methods: From 5 January 2017 to 16 April 2019, 64 patients who underwent ultrasound-guided thermal ablation with a total of 75 liver malignant tumors located in the hepatic dome were enrolled in the present study. One-lung ventilation was employed to improve the acoustic window and protect the lung and diaphragm. If the one-lung ventilation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The advantage of employing a hypodermic needle as a waveguide to deliver the acoustic energy to the target is that acoustic streaming can be generated to treat lesions within anatomical regions, such as in the lungs or in the liver, that would be difficult to reach with conventional HIFU based systems. The complication arising from using HIFU to treat lesions within the thoracic region or in the hepatic dome, for example, is mainly associated with the acoustic shadowing of bones and gas, which can hinder the formation of a proper US focus at the target [113,114]. By using an ultrasonic needle for the local administration of drugs, not only these anatomical structures could be easily bypassed, but also one could avoid side effects and complications associated with other commonly used routes of drug administration (e.g., intravenous injection, systemic administration) [115,116,117,118] and minimize side bioeffects [114,119] along the beam path that one could observe in HIU applications.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of employing a hypodermic needle as a waveguide to deliver the acoustic energy to the target is that acoustic streaming can be generated to treat lesions within anatomical regions, such as in the lungs or in the liver, that would be difficult to reach with conventional HIFU based systems. The complication arising from using HIFU to treat lesions within the thoracic region or in the hepatic dome, for example, is mainly associated with the acoustic shadowing of bones and gas, which can hinder the formation of a proper US focus at the target [113,114]. By using an ultrasonic needle for the local administration of drugs, not only these anatomical structures could be easily bypassed, but also one could avoid side effects and complications associated with other commonly used routes of drug administration (e.g., intravenous injection, systemic administration) [115,116,117,118] and minimize side bioeffects [114,119] along the beam path that one could observe in HIU applications.…”
Section: Discussionmentioning
confidence: 99%
“…However, this procedure is highly invasive, risky, and can lead to complications, thus it requires an experienced operator. 18 Also, the reflected acoustic energy may cause skin burns if uncontrolled, 19 for which reason the invasive procedure of partial rib resection has even been recently proposed and evaluated as a way to create an acoustic pathway for HIFU treatments. 18 Moreover, the translation of organs during breathing cycles can impact the precision, safety, and efficiency of the HIFU treatment methods.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that thermal ablation of liver lesions adjacent to the diaphragm is related to rare diaphragmatic hernias, increased local tumor progression (LTP) rate, and post-procedural pain 7 , 8 . Several measures have been proposed to prevent these unfavorable results, including artificial ascites, 9 one-lung ventilation, 10 and intra-abdominal carbon dioxide insufflation. 11 …”
Section: Introductionmentioning
confidence: 99%